Normative Echocardiographic Reference Values for Left Atrial and Left Ventricular Parameters - Poudel, Samir Kumar; Poudel, Lata Gautam; Sherpa, Kunjang; Gautam, Binayak; Mishra, Deepak Kumar; Chapagain, Prabha; Bhatta, Ajay; Bista, Anupam; Ghimire, Nirmal; Lamsal, Sudip; Acharya, Den Prasad; Maharjan, Kijan; et al. (Journal of National Heart and Lung Society Nepal, 2025)
Background: Amidst the various modalities of cardiac investigations, echocardiography still stands atop owing to its reliability, reproducibility, cost-effectiveness and non-invasiveness. Various diseases can have effect on heart resulting in alteration of dimensions in different parameters. Differentiating normal from abnormal is, therefore, essential for timely intervention of the pathology. International guidelines have defined the normal values which are, however, not inclusive of our population. This study has brought forward the normal ranges of different cardiac parameters in different age-groups and across genders in our population, thereby helping the practitioners and researchers to move forward for further handling of the cases in their respective field. Methods: This was a hospital-based prospective observational study conducted at National Academy of Medical Sciences, Bir Hospital, Kathmandu, Nepal. The study duration was from March 2023 to April 2025. Eight hundred fifty-three patients above 18 years of age with normal echocardiography reports that were evaluated in the Department of cardiology, Bir Hospital using transthoracic 2D echocardiography were enrolled in the study. The dimensions of left-sided cardiac structures and the doppler study were measured using standard methods.Results: A total of 853 patients were enrolled in the study with a mean age of (49.15 + 13.19) years; males comprising of 52.3% of the total population. Adults were the maximum followed by the middle-aged population. The various echocardiographic parameters showed statistically significant differences among age-groups and across genders while others did not. Most of the normal reference values are, however, lower in our population as compared to those from other various international guidelines. Conclusion: The normal reference ranges for various echocardiographic parameters for both males and females and across different age-groups in our population are towards the lower side of what have been learned from other international guidelines for echocardiography.